Diagnostic Value of Thyroid Physical Examination in the Elderly and Comparison with Ultrasonography - Gülmez, Mehmet İhsan; Aydın, Canset (ENT Updates, 2025)
This study is part of the health project called "Health screening for the elderly in Ankara" for patients aged 65 and over, with 1200 participants. Patients with missing laboratory tests (n = 59), movement disorders and/or bedridden (n = 54) were excluded from the study. PE was performed by a geriatrician or an ear, nose, and throat surgeon, and ultrasonographic evaluation was performed by a radiologist. PE and USG findings were compared. We aimed to investigate the diagnostic accuracy of physical examination (PE) of the thyroid gland (TG) in patients over 65 years of age and to assess the reliability by comparing PE with ultrasonographic (USG) examination. The median age of the patients participating in the study was 71.17. When the differences between thyroid nodules (TN), the number of TN size, and goiter detection were compared in terms of PE and USG, all values were statistically significant, and P values were <0.001. The sensitivity of PE of TG was calculated as 31.0%. In our study, the sensitivity of PE of TG in terms of TN and goiter was found to be low. The diagnostic accuracy of PE of TG is low, and therefore, its impact on clinical decision-making is limited. Furthermore, detected nodules rarely progress to clinically relevant disease, leading to overdiagnosis and overtreatment. Especially in groups at risk for nodules and malignancy, PE must be combined with imaging methods and, if necessary, pathological examination, even if nodules or goiter are not palpable in PE.